Online EFL Teaching and Learning: Advanced Grammar Class and Washback Effect in Test - Lutfiana,; Tono Suwartono, (Technium Social Sciences Journal, 2020)
This study investigates the teaching and learning English through online class and the washback effect of online testing during pandemic COVID-19 issue. The participants of this study were University EFL teacher and undergraduate students of English Education Department at Universitas Nahdlatul Ulama Purwokerto in Central Java Province, Indonesia. The data were collected through interviews, documents and pictures. Then, the data analysis technique was adopted from Spradley (1980). The finding has indicated that the teaching and learning online is realized effectively through Whatsapp Group (WAG) as the e-learning platform. There are positive and negative washback effects of online testing to the teaching and learning, exclusively in advance grammar course. The teacher becomes aware of the use of test item and online testing system. In other hand, the students intend to have well preparedness to follow the test.